2019
DOI: 10.5604/01.3001.0013.7633
|View full text |Cite
|
Sign up to set email alerts
|

Comparison results of visual and machine strength grading of Scots pine sawn timber from the Silesian Forestry Region in Poland

Abstract: Comparison results of visual and machine strength grading of Scots pine sawn timber from the Silesian Forestry Region in Poland. The paper presents an analysis of the strength grading results performed by two methods – visual (appearance) and machine, carried out for sawn timber obtained from the Silesian Forestry Region in Poland. Visual strength grading was performed in accordance with PN-D-94021:2013, while the machine strength grading with the use of MTG device from Brookhuis Electronics BV. As a result of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…As expected, and other authors had concluded [28], in maritime pine and Scots pine, in addition to the better yield of the higher strength class, a decrease in the percentage of rejection was obtained for machine grading with respect to visual grading. Visual grading of maritime pine resulted in similar yields than that obtained by Vega et al [29] for this Even though the visual grading of the studied samples did not comply with the relationships between visual grade and strength class given by EN 1912:2012 [5] for these species, a comparison between machine and visual grading was made considering the theoretical strength classes.…”
Section: Machine Grading Vs Visual Gradingsupporting
confidence: 88%
“…As expected, and other authors had concluded [28], in maritime pine and Scots pine, in addition to the better yield of the higher strength class, a decrease in the percentage of rejection was obtained for machine grading with respect to visual grading. Visual grading of maritime pine resulted in similar yields than that obtained by Vega et al [29] for this Even though the visual grading of the studied samples did not comply with the relationships between visual grade and strength class given by EN 1912:2012 [5] for these species, a comparison between machine and visual grading was made considering the theoretical strength classes.…”
Section: Machine Grading Vs Visual Gradingsupporting
confidence: 88%
“…Glued laminated timber has typical features of a solid timber: light weight, good strength, elasticity, durability, easy processing, and a unique feature (i.e., is readily shaped cross-sections). Its cross-section has a layered structure, enabling the manufacturing of components with variable cross-sectional height as needed [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figures 5 and 6 show a clear, typical, and high variance of the parameter within a given strength grade. This variance can be reduced by a more careful selection of research material, as well as by sub-dividing strength grades into smaller sub-grades [31,32]. Another possibility consists of improving the sorting methods, especially by preparing models that would provide higher correlations between the physico-mechanical properties of timber and timber strength grades.…”
Section: Resultsmentioning
confidence: 99%